2018
DOI: 10.1177/0734016818813428
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Spatial Patterns of Guardianship Through Civic Technology Platforms

Abstract: Civic technologies levy advances in digital tools to promote civic engagement, giving people a voice to participate in public decision making. While democratising participation, the use of such civic tech also leaves behind a digital trace of the behaviour of its users. This paper uses such a digital trace to explore spatial patterns in active guardianship of public space. Through mapping people's participation in a platform for reporting neighbourhood concerns (a form of digitally enabled guardianship), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Findings also indicate that data from a survey of app users can rarely represent the actual population of those using the tool, or the population residing and working in these areas [62]. While exploring spatial patterns of guardianship through civic technology platforms at the level of neighborhood units in England, Solymosi [63] found that it is possible to make use of civic tech data to explore people's engagement in guardianship and map their guardianship capacity in physical space by using digital traces of behavior available online, however, there are limitations associated with crowdsourced data as they are characterized by bias sample self-selection as well as participation inequality [62] also highlighted technological, legal, institutional, ethical, and cultural-that limits the use of apps/smartphones for planning purposes. The author emphasized that the issues of data privacy, the responsibility of actions (e.g., intervening) and accountability should be addressed before data of this kind is used [62].…”
Section: Fear Of Crime and Perceived Safety: A Socio-technical Perspectivementioning
confidence: 99%
“…Findings also indicate that data from a survey of app users can rarely represent the actual population of those using the tool, or the population residing and working in these areas [62]. While exploring spatial patterns of guardianship through civic technology platforms at the level of neighborhood units in England, Solymosi [63] found that it is possible to make use of civic tech data to explore people's engagement in guardianship and map their guardianship capacity in physical space by using digital traces of behavior available online, however, there are limitations associated with crowdsourced data as they are characterized by bias sample self-selection as well as participation inequality [62] also highlighted technological, legal, institutional, ethical, and cultural-that limits the use of apps/smartphones for planning purposes. The author emphasized that the issues of data privacy, the responsibility of actions (e.g., intervening) and accountability should be addressed before data of this kind is used [62].…”
Section: Fear Of Crime and Perceived Safety: A Socio-technical Perspectivementioning
confidence: 99%